Efektivitas Pemberian Zat Pengatur Tumbuh Campuran Bawang Merah (Allium cepa L.) dan Bonggol Pisang (Musa paradisiaca L.) terhadap Pertumbuhan Stek Batang Petunia sp. - Linna Fitriani; Reny Dwi Riastuti; Destien Atmi Arisandy; Ria Dwi Jayati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the effectiveness of giving Growth Stimulating Substances on the Growth of Cuttings of Petunia sp. The population in this study is Petunia Plants. The samples were petunia plant cuttings soaked in a natural ZPT solution mixed with shallots and banana weevils. Data collection techniques used observation sheets. The results of the study were analyzed using one way Anava.. Based on the results of the study it was found that the percentage of growing cuttings in the ZPT treatment of mixed shallots and banana weevils and harmonic ZPT had the same level of growth percentage of cuttings in the medium category. Based on statistical analysis on shoot length, the value of F = 4.393 was obtained with a significance of 0.047. In calculating the root length, the value of F = 33.831 is obtained with a significance of 0.000. Based on the results of the research that has been done, it can be concluded that the administration of a mixture of growth regulators (ZPT) of shallots (Allium cepa L) and banana weevil (Musa paradisiaca, L) is effective on the growth of petunia stem cuttings). Keywords: Effectiveness, growth, natural ZPT, Petunia sp.